In vitro anti-echinococcal and metabolic effects of metformin involve activation of AMP-activated protein kinase in larval stages of Echinococcus granulosus - Loos, Julia Alexandra (2015)
Metformin (Met) is a biguanide anti-hyperglycemic agent, which also exerts antiproliferative effects on cancer cells. This drug inhibits the complex I of the mitochondrial electron transport chain inducing a fall in the cell energy charge and leading 5'-AMP-activated protein kinase (AMPK) activation. AMPK is a highly conserved heterotrimeric complex that coordinates metabolic and growth pathways in order to maintain energy homeostasis and cell survival, mainly under nutritional stress conditions, in a Liver Kinase B1 (LKB1)-dependent manner. This work describes for the first time, the in vitro anti-echinococcal effect of Met on Echinococcus granulosus larval stages, as well as the molecular characterization of AMPK (Eg-AMPK) in this parasite of clinical importance. The drug exerted a dose-dependent effect on the viability of both larval stages. Based on this, we proceeded with the identification of the genes encoding for the different subunits of Eg-AMPK. We cloned one gene coding for the catalytic subunit (Eg-ampkα) and two genes coding for the regulatory subunits (Eg-ampkβ and Eg-ampkγ), all of them constitutively transcribed in E. granulosus protoscoleces and metacestodes. Their deduced amino acid sequences show all the conserved functional domains, including key amino acids involved in catalytic activity and protein-protein interactions. In protoscoleces, the drug induced the activation of AMPK (Eg-AMPKα-P176), possibly as a consequence of cellular energy charge depletion evidenced by assays with the fluorescent indicator JC-1. Met also led to carbohydrate starvation, it increased glucogenolysis and homolactic fermentation, and decreased transcription of intermediary metabolism genes. By in toto immunolocalization assays, we detected Eg-AMPKα-P176 expression, both in the nucleus and the cytoplasm of cells as in the larval tegument, the posterior bladder and the calcareous corpuscles of control and Met-treated protoscoleces. Interestingly, expression of Eg-AMPK. was observed in the developmental structures during the de-differentiation process from protoscoleces to microcysts. Therefore, the Eg-AMPK expression during the asexual development of E. granulosus, as well as the in vitro synergic therapeutic effects observed in presence of Met plus albendazole sulfoxide (ABZSO), suggest the importance of carrying out chemoprophylactic and clinical efficacy studies combining Met with conventional anti-echinococcal agents to test the potential use of this drug in hydatidosis therapy.